TINJAUAN STANDARISASI LABORATORIUM PEMBELAJARAN BIOLOGI DI SMA NEGERI SE- KABUPATEN PASAMAN BARAT - Apriliani, Enjang - (STKIP PGRI Sumbar, 2014)
Biology is a science that has important significance for education in schools. Laboratory standard is really needed to support the students learning biology outcomes. The objectives of learning biology will not be fully achieved in the classroom without practical activities. The variation in the biology laboratory conditions at SMAN in West Pasaman district indirectly lead to differences in laboratory standardized, but not yet revealed. This research is aimed to determine the learning biology of laboratory standardization at SMAN in West Pasaman district. This research is a descriptive research which conducted from July - September in first semester in academic year 2014/2015. The sample were all laboratories in the learning biology at SMAN that West Pasaman district consist of 11 schools. The type of data in was primary data collected directly from the respondents. The instrument was a questionnaire. The data is analyzed by using descriptive qualitative. The results of data analysis showed that the average percentage of learning biology laboratory standardization at SMAN in West Pasaman district is 57, 8% with less criteria. Therefore, it can be concluded that the learning biology laboratory at SMAN in West Pasaman district is not meet to the standards set by the Ministerial Regulation No. 24 in 2007.